MYB exhibits racially disparate expression, clinicopathologic association, and predictive potential for biochemical recurrence in prostate cancer - Mohammad Aslam Khan; Srijan Acharya; Shashi Anand; Fnu Sameeta; Paramahansa Pramanik; Christopher Keel; Seema Singh; James Elliot Carter; Santanu Dasgupta; Ajay Pratap Singh (iScience, 2023)
Summary: MYB acts as a potentiator of aggressiveness and castration resistance in prostate cancer (PCa) through aberrant activation of androgen receptor (AR) signaling. Since Black men experience higher PCa incidence and mortality than White men, we examined if MYB was differentially expressed in prostate tumors from patients of these racial backgrounds. The data reveal that aberrant MYB expression starts early in precancerous high-grade prostate intraepithelial neoplastic lesions and increases progressively in malignant cells. PCa tissues from Black patients exhibit higher MYB expression than White patients in overall and grade-wise comparisons. MYB also exhibits a positive correlation with AR expression and both display higher expression in advanced tumor stages. Notably, we find that MYB is a better predictor of biochemical recurrence than AR, pre-treatment PSA, or Gleason’s grades. These findings establish MYB as a promising molecular target in PCa that could be used for improved risk prediction and therapeutic planning.